Investigation of Layer Structured NbSe2 as an Intercalation Anode Material for Sodium-Ion Hybrid Capacitors. Issue 4 (22nd February 2019) - Subramanian, Yuvaraj; Veerasubramani, Ganesh Kumar; Park, Myung-Soo; Kim, Dong-Won
Abstract : We synthesized a layer structured NbSe2 material through gas-phase solid state reaction, and its electrochemical performance was examined as an intercalation anode for sodium-ion hybrid capacitor. The NbSe2 electrode showed a reversible capacity of 142.5 mAh g −1 at 200 mA g −1 over 100 cycles with good capacity retention of 94.0%, and it delivered a high discharge capacity of 100.7 mAh at 1000 mA g −1 . The surface capacitive process mainly contributed to the charge storage in the NbSe2 electrode. Its superior electrochemical performance arose from the layered structure of NbSe2 that offered the easy pathway for sodium ion diffusion and accommodated the volume strain during sodiation/de-sodiation processes. The sodium-ion hybrid capacitor assembled with NbSe2 anode and activated carbon cathode exhibited a high power density of 599.6 W kg −1 at energy density of 17.3 Wh kg −1 with good capacity retention of 93.2% at 300 mA g −1 after 3000 cycles. Our results demonstrate that the NbSe2 can be a promising anode material for sodium-ion hybrid capacitor.